2022
DOI: 10.1038/s41467-022-35198-1
|View full text |Cite
|
Sign up to set email alerts
|

Cell type diversity in a developing octopus brain

Abstract: Octopuses are mollusks that have evolved intricate neural systems comparable with vertebrates in terms of cell number, complexity and size. The brain cell types that control their sophisticated behavioral repertoire are still unknown. Here, we profile the cell diversity of the paralarval Octopus vulgaris brain to build a cell type atlas that comprises mostly neural cells, but also multiple glial subtypes, endothelial cells and fibroblasts. We spatially map cell types to the vertical, subesophageal and optic lo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 115 publications
5
34
0
Order By: Relevance
“…One final example of overlapping expression profiles is the colocalization of dopaminergic (TyH) and glutamatergic (vGluT and slc6a15/18) markers (Figure 6). This is consistent with observations of such cells in the developing 27 and adult 26 optic lobes. While the majority of glutamatergic neurons are not dopaminergic, we observed that the majority of dopaminergic neurons in the arm did also express both glutamatergic markers (vGluT and slc6a15/18).…”
Section: Expression Profiles Of Distinct Neuronal Populationssupporting
confidence: 93%
See 1 more Smart Citation
“…One final example of overlapping expression profiles is the colocalization of dopaminergic (TyH) and glutamatergic (vGluT and slc6a15/18) markers (Figure 6). This is consistent with observations of such cells in the developing 27 and adult 26 optic lobes. While the majority of glutamatergic neurons are not dopaminergic, we observed that the majority of dopaminergic neurons in the arm did also express both glutamatergic markers (vGluT and slc6a15/18).…”
Section: Expression Profiles Of Distinct Neuronal Populationssupporting
confidence: 93%
“…We identified these by detecting the expression of a transcript whose protein sequence is homologous to those annotated as vesicular inhibitory amino acid transporter (vIAAT) in Octopus sinensis (XP 029641102.1) and in Octopus bimaculoides (XP 014787249.1). This sequence has also been referred to as a vesicular GABA transporter (vGAT) in a recent publication 27 and appears to be indicative of GABA expression, suggesting inhibitory activity. This transcript, henceforth referred to as "vGAT", is one of the extremely scarce indicators for the presence of known inhibitory neuronal markers in the axial nerve cord (Figure 4d-h).…”
Section: Expression Profiles Of Distinct Neuronal Populationsmentioning
confidence: 99%
“…The interest raised by these findings inspired deeper examination of cephalopod nervous system, the largest, most complex, and most cell-dense among invertebrates ( Young, 1963 ; Grimaldi et al, 2007 ). A brain atlas ( Deryckere et al, 2020 ; Deryckere et al, 2021 ), massive single-cell and single-nuclei datasets ( Styfhals et al, 2022 ) were produced for O. vulgaris paralarval stages, allowing for novel insights into the characterization of molecular signatures of brain cells at early stage of development for the first time in a mollusc. A measure of the effort required, however, is given by the consideration that only for 9% of the 200,000 brain cells estimated in an octopus brain at hatching (compared to the 200 million in the adult), a single-cell expression profile could be obtained.…”
Section: Cephalopod Regeneration Todaymentioning
confidence: 99%
“…Neurons of the medulla have processes within superficial layers of the optic lobe as well as locally within the medulla, and many project axons out from the optic lobe to downstream visual areas. Recent transcriptomic studies have further revealed a rich diversity of cell types within the optic lobe, as well as extensive sub-laminar organization (Songco-Casey et al 2022; Styfhals et al 2022; Gavriouchkina et al, 2022; Duruz et al 2023).…”
Section: Introductionmentioning
confidence: 99%